Interaction of tank mix between diquat and glyphosate herbicides in desiccation of fallow land - Sousa, Ueliton Venancio de; Côrrea, Fernando Rezende; Silva, Nelmício Furtado da; Cavalcante, Wendson Soares da Silva; Ribeiro, Daniele Ferreira; Rodrigues, Estevão (Brazilian Journal of Science, 2023)
The combination of herbicides in a tank mix is a frequent and operationally convenient practice. The possibility or not of the occurrence of antagonism between associated herbicides depends on the characteristics of the herbicide, the composition of the application mixture and the target. The objective of the present study was to evaluate the interaction of the tank mixture between the herbicides diquat and glyphosate in the desiccation of fallow areas. The experiment was carried out at UniBRAS' Teaching, Research and Extension Farm - Faculdade Rio Verde, in the municipality of Rio Verde - GO. The experimental design used was randomized blocks with four replications. Treatments consisted of: T1) Diquat; T2) Diquat + Mineral Oil; T3) Diquat + Glyphosate + Mineral Oil; T4) Glyphosate + Mineral Oil; and T5) Control. Evaluations of crop phytotoxicity and weed control were carried out at 7, 14 and 21 days after application. The data were submitted to analysis of variance by the F test (p < 0.05) and the cases of significance were submitted to the Tukey mean test (p < 0.05). The isolated use of glyphosate with mineral oil showed the greatest weed control at 7, 14 and 21 days after application. Diquat alone and mixed with oil did not promote satisfactory control of the weed community, possibly this can be attributed to the higher concentration of grasses present in the area. The association of diquat with glyphosate possibly caused antagonism between the molecules.